Analysis and Interpretation of Google Trends Data on Public Interest in Cosmetic Body Procedures. (22nd February 2019) - Tijerina, Jonathan D; Morrison, Shane D; Nolan, Ian T; Vail, Daniel G; Lee, Gordon K; Nazerali, Rahim
Abstract: Background: Several online resources such as Google Trends (GT) enable plastic surgeons to track search volume trends for cosmetic procedures. Understanding these data may allow surgeons to better anticipate patients' interests and meet their needs. Objectives: The authors sought to evaluate the correlation between GT search volumes and annual surgery volumes. Methods: Search terms were generated using the "related queries" feature of GT. Data were obtained for the terms breast augmentation, buttock augmentation, buttock implants, buttock lift, calf augmentation, liposuction, lower body lift, thighplasty, abdominoplasty, and brachioplasty from January 2004 to November 2017. Annual volumes for respective procedures were obtained from statistics reports of the American Society of Plastic Surgeons (ASPS) from 2006 to 2017 and American Society of Aesthetic Plastic Surgery (ASAPS) from 2004 to 2017. Correlations were evaluated applying univariate linear regression of GT data to both ASPS and ASAPS data. Results: Geographical and temporal variations in search volume were detected during the study. Search volume trends that correlated significantly with both ASPS and ASAPS surgery volume trends were: "butt implants surgery" (ASPS: R 2 = 0.366, P = 0.049; ASAPS: R 2 = 0.380, P = 0.019); "liposuction" (ASPS: R 2 = 0.690, P = 0.002; ASAPS: R 2 = 0.578, P = 0.002); and "liposuction surgery" (ASPS: R 2 = 0.672, P = 0.002; ASAPS: R 2 = 0.476, P = 0.006). Several search terms demonstrated no significant relationships, negative correlations, or were significant with only one database. Conclusions: This study characterizes GT as a convenient and informative data set for plastic surgeons to analyze patient interest in cosmetic body-sculpting procedures. GT represents a useful instrument for tailoring marketing strategies and addressing the needs of our patient population.